Exploring the Impact of Zed Certification on Manufacturing Excellence and Environmental Responsibility - Malviya, Neelesh; Deshmukh, Harshal; Saxena, Rajiv; Malviya, Sapna (Indian Journal of Pharmaceutical Education and Research, 2026)
The ZED (Zero Defect Zero Effect) Certification is an initiative aimed at enhancing the performance and sustainability of Small and Medium Enterprises (SMEs) in India. It focuses on promoting high-quality production, minimizing defects, and reducing environmental impact. The certification encourages businesses to implement global best practices while fostering improvements in efficiency, quality, and social responsibility. The ZED Certification process is structured in multiple stages, allowing companies to progress from basic compliance to higher levels of excellence. It evaluates organizations on various criteria such as operational efficiency, resource optimization, waste management, and environmental sustainability. Achieving the ZED Certification helps businesses showcase their commitment to quality, innovation, and eco-friendly practices, which enhances their reputation in the market. Beyond internal improvements, the ZED framework aligns with India's vision of becoming a global manufacturing leader by empowering SMEs to cut costs, improve productivity, and increase their competitiveness on both national and international stages. The certification process promotes continuous improvement, helping businesses tackle challenges and remain adaptable in the face of changing market conditions. Ultimately, the ZED Certification helps organizations produce high-quality products while also encouraging a positive environmental and social impact. By adhering to the ZED principles, businesses can achieve long-term sustainable growth and create value that benefits both the economy and society.
Keywords: Zero Defect Zero Effect; SME Sustainability; Quality Production; Environmental; Responsibility